ELASTISITAS PERMINTAAN TENAGA KERJA PADA USAHA KONVEKSI SKALA MIKRO DAN KECIL - Endang Rostiana; Andika Reka Sagara (Center for Economic Studies Universitas Katolik Parahyangan, 2018)
Labor intensive in small and micro scales garment sector is very common in Soreang Village, Bandung Regency, West Java Province. The purpose of this study is to analyze the elasticity of labor demand of the labor-intensive micro-small scale garment enterprises. Sixty seven entrepreneurs were interviewed to collect primary data. Result from natural logarithm regression showed that labor demand was inelastic to the unit number of machines, wage, number of output, and firm age. These regression coefficients showed that unit of machines was complementary for labor; the wage elasticity of labor demand was negative; the increase in production output will lead to increase in labor demand; and, firm age was contributed positively to the increase in labor demand.Keywords: elasticity of labor demand; small-micro scale enterprises; garment